Differential modulation of agonist and antagonist structure activity relations for rat TRPV1 by cyclosporin A and other protein phosphatase inhibitors - Pearce, Larry V. (2008)
The transient receptor potential V1 channel (vanilloid receptor, TRPV1) represents a promising therapeutic target for inflammatory pain and other conditions involving C-fiber sensory afferent neurons. Sensitivity of TRPV1 is known to be subject to modulation by numerous signaling pathways, in particular by phosphorylation, and we wished to determine whether TRPV1 structure-activity relations could be differentially affected. We demonstrate here that the structure activity relations of TRPV1, as determined by (45)Ca(2+) uptake, were substantially altered by treatment of the cells with cyclosporin A, an inhibitor of protein phosphatase 2B. Whereas the potency of resiniferatoxin for stimulation of (45)Ca(2+) was not altered by cyclosporin A treatment, the potencies of some other agonists were increased up to 8-fold. Among antagonists examined, potencies were reduced to a lesser extent, ranging from 1–2.5 fold. Finally, the efficacy of partial agonists was increased. In contrast to cyclosporin A, okadaic acid, an inhibitor of protein phosphatases 1 and 2A, had little effect on agonist potencies, and calyculin A, an inhibitor of protein phosphatases 1 and 2A but with somewhat different selectivity from that of okadaic acid, caused changes in structure activity relations distinct from those induced by cyclosporin A. Because phosphatase activity differentially modulates the structure activity relations of TRPV1 agonists and antagonists, our findings predict that it may be possible to design agonist and antagonists selective for TRPV1 in a specific regulatory environment. A further implication is that it may be desirable to tailor screening approaches for drug discovery to reflect the desired regulatory state of the targeted TRPV1.